Ro-vibrational levels and their (e-f) splitting of acetylene molecule calculated from new potential energy surfaces. (December 2022) - Nikitin, Andrei V.; Protasevich, Alexander E.; Rodina, Alena A.; Rey, Michael; Tajti, Attila; Tyuterev, Vladimir G.
Highlights: Ab initio potential energy surface was reported. Vibrational levels of acetylene were calculated. Accurate prediction of the J dependence of ( e–f ) splitting was calculated. 13C2H2 and C2D2 vibrational energy levels were calculated . Abstract: Ro-vibrational energy levels of acetylene are reported using variational nuclear motion calculations from new ab initio and empirically optimized full six-dimensional potential energy surfaces in the ground electronic state of the acetylene molecule. The calculations account for the triple, quadruple and quintuple excitations as well as relativistic and diagonal Born-Oppenheimer corrections. Variational nuclear motion calculations were performed using the exact kinetic energy operator in orthogonal coordinates. The convergence of energy levels calculations versus the size of the vibrational basis set functions was verified. Our best ab initio potential energy surface that includes the above-mentioned contributions provides the RMS (obs.-calc.) errors of 0.95 cm −1 for five fundamental energy levels. The largest contribution to the RMS error is caused primarily by a significant deviation of the ν4 fundamental frequency. Experimental values of 120 vibrational band origins were used to empirically adjust few lower-order parameters of the potential energy surface. The average error drops down to 0.45 cm −1 or 0.25 cm −1 for empirically optimized potential energy function with two or seven adjusted parameters corresponding to quadratic force field terms and one third order term. The splitting of ( e – f ) rovibrational doublets and their J dependence were calculated with high accuracy due to the full account of Coriolis interactions. Computed ( e – f ) splittings allow one to check the correctness of the assignment of empirical energy levels. The estimation of the accuracy for the calculated vibrational levels in an extended range up to 9500 cm −1 shows that the set of ab initio vibrational levels can be used for future assignments of empirically not observed ro-vibrational energy levels. The comparison of the calculated and experimental ro-vibrational energy levels of the C2 D2 and 13 C2 H2 isotopologues is also reported.